2015
DOI: 10.1371/journal.pone.0127155
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Homeostasis and Activation Is Altered in Hyperplastic Human Papillomavirus Type 16 E7 Expressing Epidermis

Abstract: It has previously been shown that expression of human papillomavirus type 16 (HPV) E7 in epidermis causes hyperplasia and chronic inflammation, characteristics of pre-malignant lesions. Importantly, E7-expressing epidermis is strongly immune suppressed and is not rejected when transplanted onto immune competent mice. Professional antigen presenting cells are considered essential for initiation of the adaptive immune response that results in graft rejection. Langerhans cells (LC) are the only antigen presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
(48 reference statements)
1
21
1
Order By: Relevance
“…Our and other studies have shown that CXCL14 induces direct chemotaxis of various immune cells including DCs, LCs, NK, and T cells (Cicchini et al, 2016; Schaerli et al, 2005; Shurin et al, 2005). Additionally, using transgenic mouse models, it has been demonstrated that HPV16 E7 expression in the epidermis creates a strong immunosuppressive area where LC and CD8 + T cell functions are significantly suppressed (Abd Warif et al, 2015; Doan et al, 1999; Tindle et al, 2001). This immune suppression appears to be mediated by an influx of HPV16 E7-induced regulatory T (Treg) cells and tolerization of cytotoxic T cells (Doan et al, 1999; Narayan et al, 2009).…”
Section: Immune Evasion By Altering Host Gene Expressionmentioning
confidence: 99%
“…Our and other studies have shown that CXCL14 induces direct chemotaxis of various immune cells including DCs, LCs, NK, and T cells (Cicchini et al, 2016; Schaerli et al, 2005; Shurin et al, 2005). Additionally, using transgenic mouse models, it has been demonstrated that HPV16 E7 expression in the epidermis creates a strong immunosuppressive area where LC and CD8 + T cell functions are significantly suppressed (Abd Warif et al, 2015; Doan et al, 1999; Tindle et al, 2001). This immune suppression appears to be mediated by an influx of HPV16 E7-induced regulatory T (Treg) cells and tolerization of cytotoxic T cells (Doan et al, 1999; Narayan et al, 2009).…”
Section: Immune Evasion By Altering Host Gene Expressionmentioning
confidence: 99%
“…Levels of these critical antigen presenting cells are markedly reduced in HPV-containing tissues (Spinillo, Tenti et al 1993; Connor, Ferrer et al 1999; Delvenne, Hubert et al 2001; Scott, Nakagawa et al 2001; Matthews, Leong et al 2003; Hubert, Caberg et al 2005; Herman, Hubert et al 2006; Caberg, Hubert et al 2008; Caberg, Hubert et al 2009; Leong, Doorbar et al 2010). When E7 is expressed in the murine epidermis, Langerhans cells are functionally impaired in both migration and antigen uptake, with fewer dendritic processes (Abd Warif, Stoitzner et al 2015). It is possible that regulation of these transcriptional targets by E7 may be important for immune evasion by HPV.…”
Section: Other Promoters Regulated By E7mentioning
confidence: 99%
“…Uninfected keratinocytes constitutively express low levels of a variety of cytokines (Wang, Amerio et al 1999), but HPV-positive keratinocytes show significantly reduced expression of many inflammatory mediators (Arany and Tyring 1996; Fichorova and Anderson 1999; Alcocer-Gonzalez, Berumen et al 2006). HPV also inhibits the differentiation and function of Langerhans cells, interferon (IFN) responses, MHC-I expression, and other immune mediators, through the regulation of host gene transcription patterns (Spinillo, Tenti et al 1993; Bielenberg, McCarty et al 1999; Connor, Ferrer et al 1999; Georgopoulos, Proffitt et al 2000; Delvenne, Hubert et al 2001; Scott, Nakagawa et al 2001; Matthews, Leong et al 2003; Guess and McCance 2005; Hubert, Caberg et al 2005; Herman, Hubert et al 2006; Li, Ou et al 2006; Caberg, Hubert et al 2008; Caberg, Hubert et al 2009; Tirone, Peghini et al 2009; Leong, Doorbar et al 2010; Li, Deng et al 2010; Deng, Li et al 2011; Heller, Weisser et al 2011; Hong, Mehta et al 2011; Karim, Meyers et al 2011; Reiser, Hurst et al 2011; Abd Warif, Stoitzner et al 2015). HPV also has a significant impact on the growth factor environment of the host cell, thereby creating a tissue environment within which viral infection can persist (Bequet-Romero and Lopez-Ocejo 2000; Nakamura, Bodily et al 2009; Walker, Smiley et al 2011; Dimaio and Petti 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the presence of viral antigens in virtually all cases of this tumour and even the detection of anti-HPV antibodies in the peripheral blood of patients, the development of an effective immune response does not occur. Moreover, the expression of HPV E7 viral protein in infected cells has been shown to induce formation of a local, strong immunosuppression area where the functions of LC and CD8 + T cells are significantly inhibited [14]. There is also strong evidence that regulatory T cells mediate this immunotolerance of cytotoxic lymphocytes [15].…”
Section: Introductionmentioning
confidence: 99%